MicroRNA-mRNA Regulatory Networking Fine-Tunes Polyunsaturated Fatty Acid Synthesis and Metabolism in the Inner Mongolia Cashmere Goat - Xie, Yuchun; Liu, Zhihong; Guo, Juntao; Su, Xin; Zhao, Cun; Zhang, Chongyan; Qin, Qing; Dai, Dongliang; Zhao, Yanhong; Wang, Zhiying; Wang, Ruijun; Zhang, Yanjun; et al. (Frontiers in Genetics, 2021)
Fatty acid composition is an important aspect of meat quality in ruminants. Improving the beneficial fatty acid level in cashmere goat meat is important to its economic value. To investigate microRNAs (miRNAs) and mRNAs that regulate or coregulate polyunsaturated fatty acid (PUFA) synthesis and metabolism in the Inner Mongolia cashmere goat, we used longissimus dorsi muscle (WLM) and biceps femoris muscle (WBM) for transcript-level sequencing. RT-qPCR was used to evaluate the expression of mRNAs and miRNAs associated with PUFA synthesis and metabolism. The total PUFA content in the WBM was significantly higher than that in the WLM (P<0.05). Our study is the first to systematically report miRNAs in cashmere goat meat. At the mRNA level, 20375 genes were identified. ACSL1, CD36 and TECRL were at the center of a gene regulatory network and contributed significantly to the accumulation and metabolic regulation of fatty acids. At the miRNA level, 426 known miRNAs and 30 novel miRNAs were identified. KEGG analysis revealed that the miRNA target genes were involved mainly in the PPAR signaling pathway. The mRNA-miRNA coregulation analysis showed that ACSL1 was negatively targeted by nine miRNAs: chi-miR-10a-5p, chi-miR-10b-5p, chi-miR-130b-5p, chi-miR-15a-5p_R-1, chi-miR-15b-5p, chi-miR-16a-5p, chi-miR-16b-5p, chi-miR-181c-5p_R+1, and chi-miR-26b-5p. Finally, we speculated that the simultaneous silencing of ACSL1 by one or more of these nine miRNAs through PPAR signaling led to low ACSL1 expression in the WLM and, ultimately to high PUFA content in the WBM. Our study helps elucidate the metabolic regulation of fatty acids in Inner Mongolia cashmere goats.